"One must do, five reductions" qualitative analysis of the diffusion and adoption constraints in Vietnam. Issue 6 (18th August 2022) - Tuan, Le Anh; Wehmeyer, Helena; Connor, Melanie
ABSTRACT: Over the last decades, Vietnam has increased its rice production substantially, which has resulted in environmental degradation and adverse health effects. The present study aimed to document the introduction and diffusion of the sustainable technology package "One Must Do, Five Reductions" (1M5R). Barriers to adoption were investigated with 155 farmers in 17 focus group discussions. Results show that external factors such as the geographical location of farms and access to water seem to be the main barriers. Knowledge provision, demonstration fields, and access to extension services are important to increase the adoption of sustainable rice farming practices.